MENUMBUHKAN BRAND CULTURE DALAM ORGANISASI PERGURUAN TINGGI DARI PERSPEKTIF CORPORATE BRANDING - Nurul Azizah; Siti Ning Farida; Erindah Dimisyqiyani (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
The purpose of this study was to determine the influence of factors in strengthening brand cuture from a corporate branding perspective. Brand is an invisible asset whose value can exceed the visible assets in an organization. The level of awareness of the organization, especially universities, about brands is still not high, especially at the UPN